2023
DOI: 10.1007/s11604-023-01387-1
|View full text |Cite
|
Sign up to set email alerts
|

The location of unilateral axillary lymphadenopathy after COVID-19 vaccination compared with that of metastasis from breast cancer without vaccination

Abstract: Purpose Unilateral axillary lymphadenopathy is known to occur after coronavirus disease (COVID-19) vaccination. Post-vaccination lymphadenopathy may mimic the metastatic lymph nodes in breast cancer, and it is challenging to distinguish between them. This study investigated whether the localization of axillary lymphadenopathy on magnetic resonance imaging (MRI) could be used to distinguish reactive lymphadenopathy after COVID-19 vaccines from metastatic nodes. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Although it is di cult to discriminate between benign and malignant accumulation levels, Eifer et al reported that machine learning using the characteristic features of PET, CT, and PET/CT images could discriminate between reactive lymph nodes caused by COVID-19 vaccination and metastatic lymph nodes caused by breast cancer with a high rate of accuracy(13). Mukai et al reported that both ventral and dorsal lymphadenopathies are more likely to be vaccine-induced reactions than metastases(29). This may help distinguish post-vaccination lymphadenopathy from metastasis.…”
mentioning
confidence: 99%
“…Although it is di cult to discriminate between benign and malignant accumulation levels, Eifer et al reported that machine learning using the characteristic features of PET, CT, and PET/CT images could discriminate between reactive lymph nodes caused by COVID-19 vaccination and metastatic lymph nodes caused by breast cancer with a high rate of accuracy(13). Mukai et al reported that both ventral and dorsal lymphadenopathies are more likely to be vaccine-induced reactions than metastases(29). This may help distinguish post-vaccination lymphadenopathy from metastasis.…”
mentioning
confidence: 99%
“…Therefore, the present study determined the relevance of COVID-19 testing in these patients of specific IgG antibodies, their circulating time, and VNT titers post-vaccination, thus correlating long-term immunological preparedness and response to COVID-19 vaccination and/or infection. However, a clear distinction had to be made between COVID-19-related and cancer progression symptoms [ 33 ]. The latter included the clinical manifestations of cancer therapy, in particular of the immuno- and targeted anticancer therapy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…After applying the eligibility criteria, 102 studies remained, forming the evidentiary basis for the guideline recommendations: 24 systematic reviews, 11, 14 RCTs, 6,[44][45][46][47][48][49][50][51][52][53][54][55][56] and 64 nonrandomized studies. [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120] The ...…”
Section: Characteristics Of Studies Identified In the Literature Searchmentioning
confidence: 99%